In Vitro Evaluation of Antimicrobial and Biofilm-Modulating Effects of Commercial Cranberry (Vaccinium macrocarpon) Extracts Against Escherichia coli and Staphylococcus aureus - Veledar-Hamalukić, Anisa; Avdić, Monia; Demirović, Amra (Scripta Medica, 2025)
Background/Aim: Cranberry (Vaccinium macrocarpon Ait) extracts are widely recognised for their antimicrobial properties, particularly in preventing urinary tract infections (UTIs). However, their effects on biofilm formation remain underexplored. This study aimed to authenticate commercially available cranberry extracts, quantify their proanthocyanidin (PAC) content and evaluate their antimicrobial and biofilm-modulating effects against Escherichia coli and Staphylococcus aureus. Methods: Two commercially available cranberry extracts were analysed using high-performance liquid chromatography (HPLC) to confirm their authenticity based on anthocyanin profiles. PAC content was determined using a modified Bate-Smith method. Antimicrobial activity was assessed via the microbroth dilution method, determining the minimum inhibitory concentration (MIC) for each extract against two E coli and three S aureus strains. Biofilm formation was evaluated using crystal violet staining, with statistical analyses including paired sample t-tests, Friedman’s ANOVA and the Durbin-Conover test. Results: HPLC analysis confirmed that both extracts were derived from the V macrocarpon. PAC content differed significantly between samples (p < 0.001), yet MIC values remained consistent at 125 µg/mL for E coli and 250 µg/mL for S aureus. Notably, at concentrations below the MIC, both extracts unexpectedly enhanced bacterial planktonic growth and biofilm formation, likely due to quorum sensing activation. Statistical analyses revealed significant differences in biofilm formation among S aureus strains, while E coli strains showed a more uniform response. Conclusion: While cranberry extracts exhibit strong antibacterial properties at MIC levels, their ability to stimulate biofilm formation at sub-inhibitory concentrations raises concerns regarding their application. These findings highlight the need for further molecular studies to optimise cranberry-based interventions against biofilm-associated infections.